Core-shell structure sodium niobate ZnO refractive orientation piezoelectric microcrystalline nano-generator and preparation method and application thereof

By using core-shell structure sodium niobate @ZnO fold-oriented piezoelectric crystals as piezoelectric material, a high-performance piezoelectric crystal nanogenerator was prepared, which solved the problems of low energy utilization rate and unstable output performance of traditional nanopower generation devices, and achieved efficient energy collection and storage.

CN119654051APending Publication Date: 2025-03-18HUANGSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311772501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional nano-power generation devices have problems of low energy utilization and unstable output performance, which limits their use in practical applications.

Method used

A core-shell structure sodium niobate @ZnO folding orientation piezoelectric crystal is used as a piezoelectric material to prepare a high-performance piezoelectric crystal nanogenerator through laminated structure and hot pressing technology.

Benefits of technology

It has achieved improvements in piezoelectric performance and durability, and can generate voltages up to 152V, solving the problems of hard, brittle and unstable performance of piezoelectric ceramic materials in traditional nanogenerators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654051A_ABST
    Figure CN119654051A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure sodium niobate ZnO refractive orientation piezoelectric microcrystal nano generator and a preparation method and application thereof, and belongs to the technical field of micro-nano science and nano power generation. The nano-generator comprises a first PDMS insulating layer, a first PDMS / piezoelectric material composite layer, an interdigital electrode layer, a second PDMS / piezoelectric material composite layer and a second PDMS insulating layer which are stacked in sequence from bottom to top, a piezoelectric material in the composite layers is a sodium niobate (at) ZnO preferential orientation piezoelectric microcrystal of a core-shell structure, and preferential orientation sodium niobate ceramic seed crystals are prepared through a molten salt method. And then preparing sodium niobate-ZnO core-shell structure ceramic powder, wherein a zinc oxide shell layer plays a coordination role between sodium niobate ceramic crystal grains and a PDMS matrix. The nano generator prepared by the invention is excellent in piezoelectric property and durability, can generate a voltage up to 152V, and realizes collection and storage of energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of micro-nano science and nano-power generation technology, and specifically relates to a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator and a preparation method and application thereof. Background Art

[0002] Nowadays, as small and low-power micro-intelligent products become more and more common, people are faced with problems such as limited battery life and environmental pollution. Especially in areas such as space and the ocean where it is inconvenient to use batteries, it is crucial to make the device work and improve its endurance. There are various kinds of energy in our living environment, such as mechanical energy, thermal energy, wind energy, and solar energy. If we can collect various energy from the environment and convert it into electrical energy, we can achieve a sustainable supply of power for the device, and at the same time greatly promote the development of micro-intelligent devices.

[0003] Among energy harvesting devices, piezoelectric nanogenerators can capture mechanical energy and have the advantages of being weather independent, lightweight, easy to manufacture, and able to efficiently harvest energy at low frequencies, thus attracting widespread attention. However, traditional nanogenerators have the problems of low energy utilization and unstable output performance, which limits the use of nanogenerator devices in practical applications. Liu et al. proposed a single-electrode mode composite nanogenerator collector and analyzed its advantages [Liu Zhiwei, Liu Kun, Yang Shaohui, et al. Journal of Guangzhou Maritime University, 2021, 29(03):75-81+86]. Although many scientists have proposed many strategies to improve the power generation capacity of nanogenerators, these nanogenerator devices have a single structure, poor repeatability, low reliability, and low output performance, and can only drive electronic products with microwatt-level effective power. Summary of the invention

[0004] The purpose of the present invention is to provide a core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystalline nanogenerator and its preparation method and application, so as to solve the problems that the hard and brittle shortcomings of piezoelectric ceramic materials in nanogenerators lead to incompatibility between ceramic particles and the matrix, as well as poor piezoelectric performance and durability of nanogenerators.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In the first aspect, the present invention provides a core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystalline nanogenerator, which comprises, from bottom to top, a first PDMS (polydimethylsiloxane) insulating layer, a first PDMS / piezoelectric material composite layer, an interdigitated electrode layer, a second PDMS / piezoelectric material composite layer, and a second PDMS insulating layer stacked in sequence;

[0007] The thickness of the first PDMS insulating layer and the second PDMS insulating layer are the same, both of which are 50-100 μm; the thickness of the first PDMS / piezoelectric material composite layer and the second PDMS / piezoelectric material composite layer are the same, both of which are 100-250 μm; the thickness of the interdigital electrode layer is 60-120 μm.

[0008] The left and right sides of the interdigital electrode layer are respectively connected with copper wires; the copper wires are used to connect to the load circuit.

[0009] The piezoelectric material in the first PDMS / piezoelectric material composite layer and the second PDMS / piezoelectric material composite layer is a core-shell structure sodium niobate@ZnO folded preferentially oriented piezoelectric microcrystal, wherein the shell thickness of the core-shell structure is 20-50 nm; the core-shell structure sodium niobate@ZnO folded preferentially oriented piezoelectric microcrystal is prepared by the following steps:

[0010] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide to obtain a mixed powder, add molten salt, the mass ratio of the mixed powder to the molten salt is 1:1-1.3, add anhydrous ethanol and ball mill for 10-24h, dry at 60-80℃, pre-sinter at 1000-1050℃ for 2-3h, wash and dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0011] S2.B i 2.5 Na 3.5 Nb5O 18 The precursor, potassium carbonate (K2CO3) and NaCl are mixed evenly, anhydrous ethanol is added and ball-milled for 8-12 hours, dried at 60-80°C, melted at 920-980°C for 2-3 hours, washed and dried to obtain preferentially oriented NaNbO3 flaky ceramic grains;

[0012] S3. Zinc sulfate heptahydrate (ZnSO4·7H2O) and carbonamide CO(NH2)2 are dissolved in deionized water and reacted for 1-2h, and heat treated at 220-260°C for 2-3h to obtain a zinc oxide precursor mixed solution;

[0013] S4. Disperse NaNbO3 flaky ceramic grains in the zinc oxide precursor mixed solution, stir at a speed of 500r / min for 2-3h, and then precipitate in a water bath at 80-150℃ to obtain crystalline particles. Wash and dry to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

[0014] Furthermore, the molar ratio of the bismuth trioxide, sodium carbonate and niobium pentoxide is 1:1-1.5:1-1.5.

[0015] Furthermore, the molten salt is a mixture of sodium chloride (NaCl) and potassium chloride (KCl) in a molar ratio of 1:1.06.

[0016] Furthermore, the Bi 2.5 Na 3.5 Nb5O 18 The molar ratio of precursor, K2CO3 and NaCl is 1:2:3.

[0017] Furthermore, the dosage ratio of ZnSO4·7H2O, CO(NH2)2 and deionized water is 15g:6g-9g:100mL.

[0018] Furthermore, the preferred oriented NaNbO3 flaky ceramic grains have a length of 20-30 μm and a radial ratio of ≥15.

[0019] Furthermore, the dosage ratio of the NaNbO3 flaky ceramic grains and the zinc oxide precursor mixed solution is 10-20 g:100 mL.

[0020] In a second aspect, the present invention provides a method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator, comprising the following steps:

[0021] Step 1, PDMS precursor solution and cross-linking agent are mixed evenly in a mass ratio of 10:0.5-1 to remove bubbles, thereby obtaining PDMS sol; the cross-linking agent is hexane;

[0022] Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate, the spin-coating thickness of the PDMS sol is 50-100 μm, and drying at 50-80°C for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer, which plays a packaging role of insulating protection, and preparing the second PDMS insulating layer in the same way;

[0023] Step 3, core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals and PDMS sol are mixed uniformly in a mass ratio of 1:5-10 to remove bubbles, and then heated in a water bath at 60°C for 0.5-1h to obtain a composite slurry; the composite slurry is spin-coated on the first PDMS insulating layer to obtain a first PDMS / piezoelectric material composite layer 2. The spin coating thickness of the first PDMS / piezoelectric material composite layer is 100-250μm, and it is dried at 50-80°C for 3-5h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer and the first PDMS / piezoelectric material composite layer is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer in the same way to prepare a second PDMS insulating layer and a second PDMS / piezoelectric material composite layer laminated structure;

[0024] Step 4, evenly attaching the interdigital electrodes between the first PDMS / piezoelectric material composite layer and the second PDMS / piezoelectric material composite layer, and hot pressing to obtain a nanogenerator structure;

[0025] Step 5: Lead out the interdigitated electrodes with copper wires and polarize them to obtain a nanogenerator. Connect the two electrodes to a load circuit, and output electrical signals by bending and pressing to realize the nano-power generation function.

[0026] Furthermore, the spin coating speed is 1000-1500 r / min.

[0027] Furthermore, the hot pressing pressure is 30-50 MPa, the hot pressing temperature is 50-80° C., and the hot pressing time is 1 hour.

[0028] Furthermore, the polarization electric field strength is 3-10 kV / mm, and the time is 10-30 min.

[0029] In a third aspect, the present invention provides an application of a core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator in a piezoelectric micro-intelligent device.

[0030] Beneficial effects of the present invention:

[0031] 1. The present invention provides a core-shell structure sodium niobate @ ZnO folded orientation piezoelectric microcrystal nanogenerator and its preparation method and application. First, folded orientation sodium niobate ceramic seed crystals are prepared by molten salt method, and then core-shell structure sodium niobate @ ZnO folded orientation piezoelectric microcrystals are prepared as piezoelectric materials, with folded orientation sodium niobate ceramic grains as core and zinc oxide ZnO as shell. The shell layer plays a coordination role between sodium niobate ceramic grains and PDMS matrix, and the strong piezoelectric excitation coefficient of polar semiconductor ZnO is used to improve the piezoelectric output performance. Finally, after mixing with PDMS, a flexible piezoelectric film is prepared, which solves the problem of incompatibility between ceramic particles and matrix caused by the hard and brittle shortcomings of piezoelectric ceramic materials in nanogenerators, and realizes energy collection and storage.

[0032] 2. The present invention prepares a core-shell structure sodium niobate @ ZnO folded orientation piezoelectric microcrystalline nanogenerator with excellent piezoelectric performance and durability. The electric domain orientation of the folded orientation sodium niobate ceramic grains can be consistent after polarization to obtain the maximum piezoelectric output; the zinc oxide shell is conducive to capturing electrons and plays a coordinating role between the perovskite grains and the PDMS matrix. The results show that the flexible nanogenerator can generate a voltage of up to 152V, thereby realizing energy collection and storage.

[0033] 3. The present invention is low-cost and can be used for large-scale production of novel core-shell structure sodium niobate @ZnO preferentially oriented piezoelectric microcrystalline nanogenerator devices. The prepared nanogenerators can be widely used in piezoelectric micro-intelligent devices such as smart sensors, power supplies for mobile devices, and human implants, providing new ideas for the preparation and application of nanogenerators. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention will be further described below in conjunction with the accompanying drawings.

[0035] Figure 1 It is a schematic structural diagram of the core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator of the present invention;

[0036] Figure 2 is an open circuit voltage output parameter diagram of the nanogenerator prepared in Example 4 of the present invention when it is working;

[0037] Figure 3 This is a graph of the working durability times of the nanogenerator prepared in Example 4 of the present invention;

[0038] In the figure: 1. first PDMS insulating layer; 2. first PDMS / piezoelectric material composite layer; 3. interdigitated electrode layer; 4. second PDMS / piezoelectric material composite layer; 5. second PDMS insulating layer; 6. copper wire; 7. copper wire. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Please refer to Figure 1 A core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystalline nanogenerator, comprising, from bottom to top, a first PDMS insulating layer 1, a first PDMS / piezoelectric material composite layer 2, a forked electrode layer 3, a second PDMS / piezoelectric material composite layer 4, and a second PDMS insulating layer 5, wherein the left and right sides of the forked electrode layer 3 are respectively connected with a copper wire 6 and a copper wire 7;

[0041] The first PDMS insulating layer 1 and the second PDMS insulating layer 5 have the same thickness, both of which are 50-100 μm; the first PDMS / piezoelectric material composite layer 2 and the second PDMS / piezoelectric material composite layer 4 have the same thickness, both of which are 100-250 μm; the thickness of the interdigital electrode layer 3 is 60-120 μm;

[0042] The copper wire 6 and the copper wire 7 are used to connect the load circuit;

[0043] The piezoelectric material in the first PDMS / piezoelectric material composite layer 2 and the second PDMS / piezoelectric material composite layer 4 is a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystal, and the shell thickness in the core-shell structure is 20-50 nm.

[0044] The method for preparing the core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals comprises the following steps:

[0045] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide in a molar ratio of 1:1-1.5:1-1.5 to obtain a mixed powder, add molten salt (a mixture of NaCl and KCl in a molar ratio of 1:1.06), the mass ratio of the mixed powder to the molten salt is 1:1-1.3, add anhydrous ethanol and ball mill for 10-24h, dry at 60-80℃, pre-sinter at 1000-1050℃ for 2-3h, and use 60-80℃ deionized water to ultrasonically clean and remove the molten salt, and then dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0046] S2. Bi with a molar ratio of 1:2:3 2.5 Na 3.5 Nb5O 18 The precursor, K2CO3 and NaCl are mixed evenly, anhydrous ethanol is added and ball-milled for 8-12 hours, dried at 60-80°C, melted at 920-980°C for 2-3 hours, 3 mol / L dilute HNO3 is used for cleaning at a magnetic stirring speed of 300-500 r / min to remove the reaction byproduct Bi2O3, and ultrasonically cleaned and dried at 60-80°C deionized water to obtain NaNbO3 flaky ceramic grains with a length of 20-30 μm and a radial ratio of ≥15;

[0047] S3. ZnSO4·7H2O and CO(NH2)2 are dissolved in deionized water and reacted for 1-2h, and then heat treated at 220-260℃ for 2-3h to obtain a zinc oxide precursor mixed solution; the dosage ratio of ZnSO4·7H2O, CO(NH2)2 and deionized water is 15g:6g-9g:100mL;

[0048] S4. The NaNbO3 flaky ceramic grains and zinc oxide precursor mixed solution in a dosage ratio of 10-20g:100mL are evenly mixed, stirred at a speed of 500r / min for 2-3h, and then precipitated in a water bath at 80-150℃ to obtain crystalline particles. The crystalline particles are ultrasonically cleaned and dried in deionized water at 60-80℃ to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

[0049] A method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator comprises the following steps:

[0050] Step 1, PDMS prepolymer solution and hexane are mixed in a mass ratio of 10:0.5-1, stirred evenly at a speed of 300-400 r / min, and vacuumed to remove bubbles to obtain PDMS sol;

[0051] Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate at a speed of 1000-1500 r / min, the spin-coating thickness of the PDMS sol is 50-100 μm, and drying at 50-80°C for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer 1, and preparing the second PDMS insulating layer 5 in the same way;

[0052] Step 3, core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals are mixed with PDMS sol in a mass ratio of 1:5-10, and after vacuuming to remove bubbles, the mixture is heated in a water bath at 60°C and stirred (150-200r / min) for 0.5-1h to obtain a composite slurry; the composite slurry is spin-coated onto the first PDMS insulating layer 1 at a speed of 1000-1500r / min to obtain a first PDMS / piezoelectric material composite layer 2, the spin coating thickness of the first PDMS / piezoelectric material composite layer 2 is 100-250μm, and the composite film is dried at 50-80°C for 3-5h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer 1 and the first PDMS / piezoelectric material composite layer 2 is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer 5 in the same way to prepare a laminated structure of the second PDMS insulating layer 5 and the second PDMS / piezoelectric material composite layer 4;

[0053] Step 4, the interdigital electrodes 3 are evenly attached between the first PDMS / piezoelectric material composite layer 2 and the second PDMS / piezoelectric material composite layer 4, and the nanogenerator structure is obtained by hot pressing, and cut into a 5*8 cm square, with a hot pressing pressure of 30-50 MPa, a hot pressing temperature of 50-80°C, and a hot pressing time of 1 hour;

[0054] Step 5: Lead out the interdigitated electrodes 3 with copper wires and polarize them to obtain a nanogenerator. The polarization electric field strength is 3-10 kV / mm and the time is 10-30 min.

[0055] Example 1

[0056] The method for preparing core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystals comprises the following steps:

[0057] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide in a molar ratio of 1:1.25:1.25 to obtain a mixed powder, add molten salt (a mixture of NaCl and KCl in a molar ratio of 1:1.06), the mass ratio of the mixed powder to the molten salt is 1:1.15, add anhydrous ethanol and ball mill for 18h, dry at 70℃, pre-calculate at 1025℃ for 2.5h, and use 70℃ deionized water to ultrasonically clean and remove the molten salt, and then dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0058] S2. Bi with a molar ratio of 1:2:3 2.5 Na 3.5 Nb5O 18 The precursor, K2CO3 and NaCl were mixed evenly, and then ball-milled with anhydrous ethanol for 10 hours. After drying at 70°C, the mixture was melted at 950°C for 2.5 hours, and washed three times with 3 mol / L dilute HNO3 at a magnetic stirring speed of 400 r / min to remove the reaction byproduct Bi2O3. The mixture was ultrasonically cleaned and dried with deionized water at 70°C to obtain NaNbO3 flaky ceramic grains with a length of 27 μm and a radial ratio of ≥15.

[0059] S3.15g ZnSO4·7H2O and 7.5g CO(NH2)2 were dissolved in 100mL deionized water and reacted for 1.5h, and then heat treated at 240℃ for 2.5h to obtain a zinc oxide precursor mixed solution;

[0060] S4. The NaNbO3 flaky ceramic grains and zinc oxide precursor mixed solution in a dosage ratio of 15.9g:100mL were mixed evenly, stirred at a speed of 500r / min for 2.5h, and then precipitated in a water bath at 115℃ to obtain crystalline particles. The particles were ultrasonically cleaned and dried in deionized water at 70℃ to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

[0061] Example 2

[0062] The method for preparing core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystals comprises the following steps:

[0063] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide in a molar ratio of 1:1:1 to obtain a mixed powder, add molten salt (a mixture of NaCl and KCl in a molar ratio of 1:1.06), the mass ratio of the mixed powder to the molten salt is 1:1, add anhydrous ethanol and ball mill for 18h, dry at 70℃, pre-calculate at 1025℃ for 2.5h, and use 70℃ deionized water to ultrasonically clean and remove the molten salt, and then dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0064] S2. Bi with a molar ratio of 1:2:3 2.5 Na 3.5 Nb5O 18 The precursor, K2CO3 and NaCl were mixed evenly, and then ball-milled with anhydrous ethanol for 10 hours. After drying at 70°C, the mixture was melted at 950°C for 2.5 hours, and washed three times with 3 mol / L dilute HNO3 at a magnetic stirring speed of 400 r / min to remove the reaction byproduct Bi2O3. The mixture was ultrasonically cleaned and dried with deionized water at 70°C to obtain NaNbO3 flaky ceramic grains with a length of 29 μm and a radial ratio of ≥15.

[0065] S3.15g ZnSO4·7H2O and 6.5g CO(NH2)2 were dissolved in 100mL deionized water and reacted for 1.5h, and then heat treated at 240℃ for 2.5h to obtain a zinc oxide precursor mixed solution;

[0066] S4. NaNbO3 flaky ceramic grains and zinc oxide precursor mixed solution in a dosage ratio of 12g:100mL were mixed evenly, stirred at a speed of 500r / min for 2.5h, and then precipitated in a water bath at 115℃ to obtain crystalline particles. The particles were ultrasonically cleaned and dried in deionized water at 70℃ to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

[0067] Example 3

[0068] The method for preparing core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystals comprises the following steps:

[0069] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide in a molar ratio of 1:1.5:1.5 to obtain a mixed powder, add molten salt (a mixture of NaCl and KCl in a molar ratio of 1:1.06), the mass ratio of the mixed powder to the molten salt is 1:1.3, add anhydrous ethanol and ball mill for 18h, dry at 70℃, pre-calculate at 1025℃ for 2.5h, and use 70℃ deionized water to ultrasonically clean and remove the molten salt, and then dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0070] S2. Bi with a molar ratio of 1:2:3 2.5 Na 3.5 Nb5O 18The precursor, K2CO3 and NaCl were mixed evenly, and then ball-milled with anhydrous ethanol for 10 hours. After drying at 70°C, the mixture was melted at 950°C for 2.5 hours, and washed three times with 3 mol / L dilute HNO3 at a magnetic stirring speed of 400 r / min to remove the reaction byproduct Bi2O3. The mixture was ultrasonically cleaned and dried with deionized water at 70°C to obtain NaNbO3 flaky ceramic grains with a length of 23 μm and a radial ratio of ≥15.

[0071] S3.15g ZnSO4·7H2O and 9g CO(NH2)2 were dissolved in 100mL deionized water and reacted for 1.5h, and then heat treated at 240℃ for 2.5h to obtain a zinc oxide precursor mixed solution;

[0072] S4. The NaNbO3 flaky ceramic grains and zinc oxide precursor mixed solution in a dosage ratio of 20g:100mL were mixed evenly, stirred at a speed of 500r / min for 2.5h, and then precipitated in a water bath at 115℃ to obtain crystalline particles. The crystalline particles were ultrasonically cleaned and dried in deionized water at 70℃ to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

[0073] Comparative Example 1

[0074] The method for preparing preferentially oriented NaNbO3 flaky ceramic grains comprises the following steps:

[0075] S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide in a molar ratio of 1:1.25:1.25 to obtain a mixed powder, add molten salt (a mixture of NaCl and KCl in a molar ratio of 1:1.06), the mass ratio of the mixed powder to the molten salt is 1:1.15, add anhydrous ethanol and ball mill for 18h, dry at 70℃, pre-calculate at 1025℃ for 2.5h, and use 70℃ deionized water to ultrasonically clean and remove the molten salt, and then dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor;

[0076] S2.B i 2.5 Na 3.5 Nb5O 18 The precursor, K2CO3 and NaCl were mixed evenly, and then ball-milled with anhydrous ethanol for 10 hours. After drying at 70°C, the mixture was melted at 950°C for 2.5 hours, and washed three times with 3 mol / L dilute HNO3 at a magnetic stirring speed of 400 r / min to remove the reaction byproduct Bi2O3. The mixture was ultrasonically cleaned and dried with deionized water at 70°C to obtain NaNbO3 flaky ceramic grains with a length of 27 μm and a radial ratio of ≥15.

[0077] Example 4

[0078] A method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator comprises the following steps:

[0079] Step 1, PDMS prepolymer solution and hexane are mixed in a mass ratio of 10:0.75, stirred evenly at a speed of 350 r / min, and vacuumed to remove bubbles to obtain PDMS sol;

[0080] Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate at a speed of 1250 r / min, the spin-coating thickness of the PDMS sol is 75 μm, and drying at 65° C. for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer 1, and preparing the second PDMS insulating layer 5 in the same manner;

[0081] Step 3, core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals (prepared in Example 1) are mixed with PDMS sol at a mass ratio of 1:7.5, and after vacuuming to remove bubbles, the mixture is heated in a water bath at 60°C and stirred (180r / min) for 0.75h to obtain a composite slurry; the composite slurry is spin-coated onto the first PDMS insulating layer 1 at a speed of 1250r / min to obtain a first PDMS / piezoelectric material composite layer 2, the spin-coating thickness of the first PDMS / piezoelectric material composite layer 2 is 180μm, and the composite film is dried at 65°C for 4h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer 1 and the first PDMS / piezoelectric material composite layer 2 is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer 5 in the same way to prepare a laminated structure of the second PDMS insulating layer 5 and the second PDMS / piezoelectric material composite layer 4;

[0082] Step 4, the interdigital electrode 3 is evenly attached between the first PDMS / piezoelectric material composite layer 2 and the second PDMS / piezoelectric material composite layer 4, and the nanogenerator structure is obtained by hot pressing, and cut into a 5*8 cm square, with a hot pressing pressure of 40 MPa, a hot pressing temperature of 65°C, and a hot pressing time of 1 h;

[0083] Step 5: Lead out the interdigitated electrodes 3 with copper wires and polarize them to obtain a nanogenerator. The polarization electric field strength is 8 kV / mm and the time is 20 min.

[0084] Example 5

[0085] A method for preparing a core-shell structured sodium niobate @ ZnO preferentially oriented piezoelectric microcrystal nanogenerator, wherein the specific preparation method and parameters are the same as those of Example 4, except that in step 3, the core-shell structured sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals are prepared by Example 2.

[0086] Example 6

[0087] A method for preparing a core-shell structured sodium niobate @ ZnO preferentially oriented piezoelectric microcrystal nanogenerator, wherein the specific preparation method and parameters are the same as those of Example 4, except that in step 3, the core-shell structured sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals are prepared by Example 3.

[0088] Example 7

[0089] A method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator comprises the following steps:

[0090] Step 1, PDMS prepolymer solution and hexane are mixed in a mass ratio of 10:0.5, stirred evenly at a speed of 350 r / min, and vacuumed to remove bubbles to obtain PDMS sol;

[0091] Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate at a speed of 1250 r / min, the spin-coating thickness of the PDMS sol is 75 μm, and drying at 65° C. for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer 1, and preparing the second PDMS insulating layer 5 in the same manner;

[0092] Step 3, core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals (prepared in Example 1) are mixed with PDMS sol at a mass ratio of 1:5.5, and after vacuuming to remove bubbles, the mixture is heated in a water bath at 60°C and stirred (180r / min) for 0.75h to obtain a composite slurry; the composite slurry is spin-coated onto the first PDMS insulating layer 1 at a speed of 1250r / min to obtain a first PDMS / piezoelectric material composite layer 2, the spin-coating thickness of the first PDMS / piezoelectric material composite layer 2 is 180μm, and the composite film is dried at 65°C for 4h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer 1 and the first PDMS / piezoelectric material composite layer 2 is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer 5 in the same way to prepare a laminated structure of the second PDMS insulating layer 5 and the second PDMS / piezoelectric material composite layer 4;

[0093] Step 4 and step 5 are the same as in Example 4.

[0094] Example 8

[0095] A method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator comprises the following steps:

[0096] Step 1, PDMS precursor solution and hexane are mixed in a mass ratio of 10:1, stirred evenly at a speed of 350 r / min, and vacuumed to remove bubbles to obtain a PDMS sol;

[0097] Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate at a speed of 1250 r / min, the spin-coating thickness of the PDMS sol is 75 μm, and drying at 65° C. for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer 1, and preparing the second PDMS insulating layer 5 in the same manner;

[0098] Step 3, core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals (prepared in Example 1) are mixed with PDMS sol in a mass ratio of 1:10, and after vacuuming to remove bubbles, the mixture is heated in a water bath at 60°C and stirred (180r / min) for 0.75h to obtain a composite slurry; the composite slurry is spin-coated onto the first PDMS insulating layer 1 at a speed of 1250r / min to obtain a first PDMS / piezoelectric material composite layer 2, the spin-coating thickness of the first PDMS / piezoelectric material composite layer 2 is 180μm, and the composite film is dried at 65°C for 4h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer 1 and the first PDMS / piezoelectric material composite layer 2 is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer 5 in the same way to prepare a laminated structure of the second PDMS insulating layer 5 and the second PDMS / piezoelectric material composite layer 4;

[0099] Step 4 and step 5 are the same as in Example 4.

[0100] Comparative Example 2

[0101] A method for preparing a sodium niobate preferentially oriented piezoelectric microcrystalline nanogenerator comprises the following steps:

[0102] Step 1 and step 2 are the same as in Example 4;

[0103] Step 3, preferentially oriented NaNbO3 flaky ceramic grains (prepared in comparative example 1) are mixed with PDMS sol in a mass ratio of 1:7.5, and after vacuuming to remove bubbles, the mixture is heated in a water bath at 60°C and stirred (180r / min) for 0.75h to obtain a composite slurry; the composite slurry is spin-coated onto the first PDMS insulating layer 1 at a speed of 1250r / min to obtain a first PDMS / piezoelectric material composite layer 2, the spin-coating thickness of the first PDMS / piezoelectric material composite layer 2 is 180μm, and the composite film is dried at 65°C for 4h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer 1 and the first PDMS / piezoelectric material composite layer 2 is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer 5 in the same way to prepare a laminated structure of the second PDMS insulating layer 5 and the second PDMS / piezoelectric material composite layer 4;

[0104] Step 4 and step 5 are the same as in Example 4.

[0105] The output piezoelectric performance of the nanogenerators prepared in Examples 4 to 8 and Comparative Example 2 was tested. Table 1 shows the maximum operating voltages that can be generated by the nanogenerators prepared in Examples 4 to 8 and Comparative Example 2 when they are working.

[0106] Table 1

[0107] Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 2 Voltage (V) 152 143 145 150 149 112

[0108] Figure 2 is the open circuit voltage output parameter of the nanogenerator prepared in Example 4 of the present invention when it is working. It can be seen that under the application of dynamic pressure, the nanogenerator can convert mechanical energy into electrical energy output; from Table 1 and Figure 2 It can be seen that the nanogenerator prepared by the present invention has stable performance, the zinc oxide shell is conducive to capturing electrons, and plays a coordinating role between the perovskite grains and the PDMS matrix to effectively improve the piezoelectric output, and the maximum output voltage can reach 152V.

[0109] Durability test:

[0110] In order to test the durability of the nanogenerator, the nanogenerator obtained in Example 4 was repeatedly pressed by an electric motor, and the open circuit voltage was measured as follows: Figure 3 As shown in Figure 2, the output open circuit voltage of the nanogenerator decreases with repeated pressing. 6 After a pressing cycle, the output voltage dropped slightly from the initial 152V to 145V, and the change range remained within 5%, indicating that the nanogenerator has good durability.

[0111] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator, comprising, from bottom to top, a first PDMS insulating layer (1), a first PDMS / piezoelectric material composite layer (2), an interdigitated electrode layer (3), a second PDMS / piezoelectric material composite layer (4), and a second PDMS insulating layer (5), characterized in that: The piezoelectric material in the first PDMS / piezoelectric material composite layer (2) and the second PDMS / piezoelectric material composite layer (4) is a core-shell structured sodium niobate@ZnO folded preferentially oriented piezoelectric microcrystal; the core-shell structured sodium niobate@ZnO folded preferentially oriented piezoelectric microcrystal is prepared by the following steps: S1. Mix bismuth trioxide, sodium carbonate and niobium pentoxide to obtain a mixed powder, add molten salt, and ball mill with anhydrous ethanol for 10-24h, dry at 60-80℃, pre-sinter at 1000-1050℃ for 2-3h, wash and dry to obtain Bi 2.5 Na 3.5 Nb5O 18 Precursor; S2.Bi 2.5 Na 3.5 Nb5O 18 The precursor, K2CO3 and NaCl are mixed evenly, anhydrous ethanol is added for ball milling for 8-12 hours, dried at 60-80°C, melted at 920-980°C for 2-3 hours, washed and dried to obtain preferentially oriented NaNbO3 flaky ceramic grains; S3. ZnSO4·7H2O and CO(NH2)2 are dissolved in deionized water and reacted for 1-2h, and then heat treated at 220-260℃ for 2-3h to obtain a zinc oxide precursor mixed solution; S4. Disperse NaNbO3 flaky ceramic grains in the zinc oxide precursor mixed solution, stir at a speed of 500r / min for 2-3h, and then precipitate in a water bath at 80-150℃ to obtain crystalline particles. Wash and dry to obtain core-shell structured sodium niobate@ZnO preferentially oriented piezoelectric microcrystals.

2. The core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 1, characterized in that: The molar ratio of bismuth trioxide, sodium carbonate and niobium pentoxide in S1 is 1:1-1.5:1-1.5; the mass ratio of the mixed powder to the molten salt is 1:1-1.3; the Bi in S2 2.5 Na 3.5 Nb5O 18 The molar ratio of the precursor, K2CO3 and NaCl is 1:2:3; the dosage ratio of ZnSO4·7H2O, CO(NH2)2 and deionized water in the S3 is 15g:6g-9g:100mL; the dosage ratio of NaNbO3 flaky ceramic grains and zinc oxide precursor mixed solution in the S4 is 10-20g:100mL.

3. The core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 1, characterized in that: The molten salt in S1 is a mixture of NaCl and KCl in a molar ratio of 1:1.

06.

4. The core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 1, characterized in that: The first PDMS insulating layer 1 and the second PDMS insulating layer 5 have the same thickness, both of which are 50-100 μm; the first PDMS / piezoelectric material composite layer 2 and the second PDMS / piezoelectric material composite layer 4 have the same thickness, both of which are 100-250 μm; and the thickness of the interdigital electrode layer 3 is 60-120 μm.

5. The core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 1, characterized in that: The left and right sides of the interdigital electrode layer 3 are respectively connected with a copper wire (6) and a copper wire (7), and the copper wire (6) and the copper wire (7) are used to connect a load circuit.

6. A method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, PDMS precursor solution and hexane are mixed evenly in a mass ratio of 10:0.5-1 to remove bubbles and obtain PDMS sol; Step 2, spin-coating the PDMS sol on the Pt(111) / TiO2 / SiO2 / Si(100) substrate, the spin-coating thickness of the PDMS sol is 50-100 μm, and drying at 50-80° C. for 0.5 h to obtain an incompletely cured wet film as the first PDMS insulating layer (1), and the second PDMS insulating layer (5) is prepared in the same manner; Step 3, the core-shell structure sodium niobate @ ZnO preferentially oriented piezoelectric microcrystals and PDMS sol are mixed uniformly in a mass ratio of 1:5-10 to remove bubbles, and then heated in a water bath at 60°C for 0.5-1h to obtain a composite slurry; the composite slurry is spin-coated on the first PDMS insulating layer (1) to obtain a first PDMS / piezoelectric material composite layer (2), the spin-coating thickness of the first PDMS / piezoelectric material composite layer (2) is 100-250μm, and dried at 50-80°C for 3-5h to obtain a fully cured composite film, and the laminated structure of the first PDMS insulating layer (1) and the first PDMS / piezoelectric material composite layer (2) is peeled off from the substrate; the composite slurry is spin-coated on the second PDMS insulating layer (5) in the same way to prepare a laminated structure of the second PDMS insulating layer (5) and the second PDMS / piezoelectric material composite layer (4); Step 4, evenly attaching the interdigital electrodes (3) between the first PDMS / piezoelectric material composite layer (2) and the second PDMS / piezoelectric material composite layer (4), and hot pressing to obtain a nanogenerator structure; Step 5: Lead out the interdigitated electrodes (3) with copper wires and polarize them to obtain a nanogenerator.

7. The method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 6, characterized in that: The rotation speed of the spin coating is 1000-1500 r / min.

8. The method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 6, characterized in that: The hot pressing pressure is 30-50 MPa, the hot pressing temperature is 50-80° C., and the hot pressing time is 1 hour.

9. The method for preparing a core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to claim 6, characterized in that: The polarization electric field strength is 3-10 kV / mm, and the polarization time is 10-30 min.

10. Application of the core-shell structure sodium niobate@ZnO preferentially oriented piezoelectric microcrystalline nanogenerator according to any one of claims 1 to 5 in piezoelectric micro-intelligent devices.